Evolution of Corporate Legal Functions and Their Impact on Banking Sector Financial Performance - Adi Dwi Putranto; Riza Pahlevi; Susilo Toto Raharjo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The evolution of the corporate legal function has shifted its role from traditional compliance toward a strategic enabler of governance and value creation in banking, amid complex regulatory and digital landscapes. This study aims to analyze how the evolution of corporate legal functions influences banking sector financial performance through a systematic literature review. This systematic literature review analyzes 26 peer-reviewed studies from 2015 to 2025 using thematic synthesis aligned with PRISMA guidelines. Four dimensions emerge: expansion from compliance to value creation; legal environments’ influence on bank profitability and efficiency; integration of corporate legal governance with strategic financial management; and legal risk management’s role in fostering compliance culture and sustainable finance. Findings indicate Legal Officers act as crucial mediators balancing regulatory adherence, risk mitigation, and strategic financial objectives, enhancing operational resilience, investor confidence, and sustainable outcomes. The study underscores legal harmonization and ethical governance’s rising importance in digital banking, contributing a Legal-Performance Integration Framework (LPIF) to advance theory and practice in banking legal governance.